The Impact of Levothyroxine and Testosterone Administration on Bladder Contractility in the Rat Model of Propylthiouracil-Induced Hypothyroidism - Didem Yılmaz Oral; Berna Güven Ciloğlu; Serap Gür (Urology Research and Practice)
Objective: To investigate the effects of testosterone (T) treatment, with or without levothyroxine, the most widely used and least effective medication for managing hypothyroidism, on the functional and histological changes in propylthiouracil (PTU)- induced hypothyroid rat bladders.